Estrutura e influência da sazonalidade na comunidade de borboletas da subfamília Ithomiinae (Lepidoptera: Nymphalidae) na Estação Científica Ferreira Penna, Melgaço, Pará - ARAÚJO, Ivanei Souza (Universidade Federal do Pará, 2013)
The Neotropical ithomiine butterflies (Lepidóptera: Nymphalidae: Ithomiinae) are the models in mimicry rings and are relatively well known taxonomically. For these reasons, they are often chosen as biological indicator species. The present study was undertaken to characterize the ithomiine community in dense evergreen upland tropical rain forest at the Ferreira Penna Scientific Station in the Caxiuanã National Forest, municipality of Melgaço, Pará, Brazil, as well as to test the efficiency of the sampling protocol for this group of butterflies. In a forested area of 500 by 500 m, collections were made with two methods. Trapping was done during five consecutive days per month with baits of Heliotropium indicum leaves and flowers within five 100 by 100 m parcels, each of which contained five understory and five canopy traps. On the same days, in nearby areas, manual capture was undertaken with entomological hand nets. Sampling was done in July and October 2004 and January to November 2005. Collection effort was 2000 trap-hours per month and 40 net-hours per month. A total of 1844 ithomiine butterflies (14 species) was collected. Hypothyris ninonia (Hübner, [1806]) and Napeogenes rhezia (Geyer, [1834]) were the most abundant species. Both horizontal and vertical diversity were homogeneous, in spite of a tendency for most species to exhibit a preference for the understory. Sex ratios were unbalanced, and males were more common in the research area, but this could be an artifact of collection methods since only males are attracted to the alkaloid-bearing baits. Both collection methods showed similar species richness, even though three species were caught only by hand netting and two only in the baited traps. More specimens of Methona sp. were caught by hand netting than by trapping, indicating that this species is less attracted to the bait. Total ithomiine catch was inversely correlated with rainfall. The research area has few ithomiine species, including both common and rare species, whose abundance varies with the yearly rainfall pattern. Traps in the forest understory baited with the alkaloid source were most efficient, and their use is recommended for ithomiine community sampling.